PENGARUH KOMPETENSI, PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR SEKRETARIAT DAERAH KABUPATEN MAJENE - Arifhan Ady Dj; Wahdaniah Wahdaniah (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the effect of competence, career development on the performance of civil servants at the regional secretariat office of Majene Regency. Associative quantitative method was used in this study, and used a questionnaire as a data collection tool. The research data was processed using multiple linear regression analysis. The results show that competence, career development has a positive relationship to the performance of civil servants in the regional secretariat office of Majene Regency